POLITIK EKONOMI PERTEMBAKAUAN DI KABUPATEN TEMANGGUNG TOBACCO POLITICAL ECONOMY IN TEMANGGUNG DISTRICT - Kharisma Melati; Teguh Yuwono (Journal of Politic and Government Studies, 2020)
This study discusses government policies related to the political economy of tobacco inTemanggung. Policies related to the FCTC agenda, PP 109/2012 and policies on loosening oftobacco imports are very difficult for farmers to cause social protests because they create a crisisthat threatens farmers social welfare. History records that the emergence of social protestmovements from the peasantry in opposing the domination of power and the policies of theauthorities became a force that cannot be underestimated. Social protest in Temanggung bornsince 80s. Starting from the endless of pros cons tobacco issue, this condition is heightenedwhen the government makes a PP 109/2012 which potentially threaten the survival of thetobacco farmers. Farmers move.This study uses qualitative methods. Researchers used purposive sampling method with thenumber of respondents 15 respondents and uses interview techniques to obtain in-depth data.From this study, it was found that the factor levels of economic status, education level, tenurestatus, political interest and political efficacy significantly influence participation rates oftobacco farmers in social protest. The social protest of tobacco farmers in Temanggung was ableto make the government re- reviewing the rules that have been made previously. This isevidenced by the inclusion of RUU Pertembakauan on Legislation 2013 although until now theBill has not yet been ratified into law.Keywords: Policies, Economic Crisis and Social Protest